Emotional Intelligence and its Adolescents Being an Exemplary - Ustin Pavel Nikolaevich; Sharafitdinov Abdulla XXX; Yusupov Umidjon Salim Salim ugli (Genius Journals, 2022)
This article focuses on the formation of emotional intelligence in adolescence and its psychological characteristics. Interrelated aspects of emotional-volitional and cognitive processes in adolescence are studied and the levels of emotional intelligence are described separately
Keywords: Adolescence; emotional experiences; cognitive processes; intellectual analysis